2015
DOI: 10.1155/2015/932512
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Residual Stress for Making Artificial Stress Corrosion Crack in the STS 304 Pipe

Abstract: The stress corrosion crack is one of the fracture phenomena for the major structure components in nuclear power plant. During the operation of a power plant, stress corrosion cracks are initiated and grown especially in dissimilar weldment of primary loop components. In particular, stress corrosion crack usually occurs when the following three factors exist at the same time: susceptible material, corrosive environment, and tensile stress (residual stress included). Thus, residual stress becomes a critical fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It is found that the high hydrostatic pressure, low hydrogen, and temperature trigger localized corrosion induced SCC [4,5]. Various efforts have been conducted to understand and mitigate the SCC in stainless steels and their welding joints; however, these studies mostly focus on the welding joints of similar metals while the real challenge in dissimilar metal welds is still overlooked [6][7][8]. Dissimilar welding promotes a strenuous task due to the melting point difference [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the high hydrostatic pressure, low hydrogen, and temperature trigger localized corrosion induced SCC [4,5]. Various efforts have been conducted to understand and mitigate the SCC in stainless steels and their welding joints; however, these studies mostly focus on the welding joints of similar metals while the real challenge in dissimilar metal welds is still overlooked [6][7][8]. Dissimilar welding promotes a strenuous task due to the melting point difference [9].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the fusion line is located between the weld zone and the heat-affected zone, and the heterogeneity of material microstructure and mechanical properties is significant. ere is a high probability of brittle fracture and initiation of welding cracks in the area around the fusion line, which is usually the weak link of welded joints [26,27]. For example, Figure 1(b) shows the fracture of the cutting pick base of the coal mine tunnel boring machine.…”
Section: Geometric Model and Methodologymentioning
confidence: 99%
“…Thus, two of the SCC's three components already exist in the weld joints, and when the weld joints are exposed to a corrosive environment, SCC can occur. The SCC behavior of fusion welding has been investigated using both experimental and numerical approaches via quantitative and qualitative methods [11][12][13][14][15][16][17]. Kim et al [11] studied the effect of residual stress on the SCC growth in GTAW joints.…”
Section: Figure 1 Stress Corrosion Crackingmentioning
confidence: 99%